Pelatihan Peningkatan Kapasitas Lembaga Ekonomi dan Kelompok Usaha Masyarakat di Desa dan Kelurahan Lokasi Program OVOP Kabupaten Flores Timur - Brigita Elisabet KR. Uran (FKIP, Universitas Palangka Raya, 2026)
This community service program aimed to strengthen the capacity of economic institutions and community business groups in villages and urban areas within the OVOP program locations in East Flores Regency. The program responded to the growing need for adaptive business strategies in the digital era and the importance of developing local potential into competitive products. It was implemented through a participatory, educative, and applicative approach during September 8–12, 2025. The training methods included lectures, interactive discussions, case studies, hands-on practice, and simulations to ensure a balance between theoretical understanding and practical application. The findings indicate significant improvements in participants’ understanding of the OVOP concept, managerial competencies, financial administration, and technical skills in product processing, packaging, and labeling. In addition, participants demonstrated increased awareness and ability in applying digital marketing strategies to expand market reach. The program also fostered stronger collaboration networks among business groups, economic institutions, and local government stakeholders. High participant engagement and active involvement throughout the sessions reflect the effectiveness of the training design. Overall, this program contributes to enhancing local economic resilience and promoting sustainable, competitive, and community-based enterprises. The study highlights the importance of continuous mentoring, institutional strengthening, and policy support to sustain the long-term impact of capacity-building initiatives in rural and semi-urban areas.